DEVELOPING INCLUSIVE TOURISM: IMPLEMENTATION OF TOURISM PRINCIPLES AT BIRA BEACH, SOUTH SULAWESI - Andi Fatimah Maoudy A. Bakty; Darwis; Mia Rahayu; Nur Farah Fajriaty Muchlis (Politeknik Pariwisata Makassar, 2025)
This study explores the implementation of inclusive tourism at Bira Beach, Bulukumba Regency, South Sulawesi, focusing on accessibility and local community empowerment as key components of sustainable coastal tourism. Although Bira Beach possesses exceptional natural potential, several challenges remain—particularly limited accessibility for people with disabilities and insufficient community involvement in destination management. Using a qualitative evaluative approach, this research applies the Universal Design Principles framework combined with community empowerment theory to assess the effectiveness of inclusive tourism development programs. Data were obtained through interviews, participatory observation, and documentation involving local residents, tourism stakeholders, and government representatives. The findings indicate that accessibility facilities, such as ramps, special toilets, and digital information systems, are still inadequate, resulting in unequal opportunities for all visitors. In addition, local communities are mostly involved in small-scale tourism activities and have limited participation in strategic decision-making processes. This condition constrains the realization of sustainable and inclusive tourism benefits. The study recommends improving physical and digital accessibility, enhancing training and capacity-building programs for local residents, and strengthening collaboration between government, private sectors, and non-governmental organizations. The integration of inclusive design and community empowerment can support Bira Beach’s transformation into an accessible and sustainable marine tourism destination that benefits all stakeholders.